Opposite Worlds, Singular Mission: Teaching as an ITA. (June 2014) - Mutua, Consolata Nthemba
Abstract : This chapter presents an autoethnography of an international graduate teaching assistant (ITA) at two universities (in a midsize state university in the eastern United States and a large public research university in the southwestern United States). Standpoint and muted group theories are utilized to discuss the experiences of being a female ITA from Africa.